2005
DOI: 10.1109/tmtt.2005.845188
|View full text |Cite
|
Sign up to set email alerts
|

A positive future for double-negative metamaterials

Abstract: Metamaterials (MTMs), which are formed by embedding inclusions and material components in host media to achieve composite media that may be engineered to have qualitatively new physically realizable response functions that do not occur or may not be easily available in nature, have raised a great deal of interest in recent years. In this paper, we highlight a large variety of the physical effects associated with double-and single-negative MTMs and some of their very interesting potential applications. The pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
227
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(232 citation statements)
references
References 99 publications
(122 reference statements)
4
227
0
1
Order By: Relevance
“…The microstrip antennas are enriched by revolution in electronic circuitry, which lead to miniaturization and integration of antenna in wireless communication devices. Techniques of miniaturization, bandwidth and gain enhancement of microstrip Patch Antenna is an active area for current research topics as on today requirement for compact designs is increasing vastly [2][3][4][5][6]. Frequency selective surfaces and Metamaterials are periodic conductive surfaces, which are artificially made to increase the performance of Antenna for communication system.…”
Section: Introductionmentioning
confidence: 99%
“…The microstrip antennas are enriched by revolution in electronic circuitry, which lead to miniaturization and integration of antenna in wireless communication devices. Techniques of miniaturization, bandwidth and gain enhancement of microstrip Patch Antenna is an active area for current research topics as on today requirement for compact designs is increasing vastly [2][3][4][5][6]. Frequency selective surfaces and Metamaterials are periodic conductive surfaces, which are artificially made to increase the performance of Antenna for communication system.…”
Section: Introductionmentioning
confidence: 99%
“…We intend to introduce a class of materials called double zero (DZR) metamaterials [1][2][3][4][5][6][7][8][9], of which the permittivity and permeability are purely imaginary [namely Re(ε r ) = 0 & Re(µ r ) = 0]. Similarly, we may consider epsilon zero (EZR) metamaterials, of which the permittivity is purely imaginary [namely Re(ε r ) = 0 & Re(µ r ) = 0] and mu zero (MZR) metamaterials, of which the permeability is purely imaginary [namely Re(ε r ) = 0 & Re(µ r ) = 0].…”
Section: Introductionmentioning
confidence: 99%
“…Such a topic has recently received a renewed interest as a consequence that experimental evidence of left-handed (LH) materials properties has been given by Smith et al [3,4] who demonstrated an LH structure made of negative-ε thin-wires and negative-µ split-ring resonators exhibiting anomalous refraction at the boundary. Since then many different applications of metamaterials have been developed [5][6][7]. Among the others, artificial transmission lines have been presented which can mimic the propagation characteristics of TEM-based transmission systems filled with homogeneous, linear and isotropic negative refraction index bulk media.…”
Section: Introductionmentioning
confidence: 99%